The mechanism of checks and balances as a method of constitutional conflicts solving: comparative law issues - I. Tretyak (Правоприменение)
The subject. The paper is devoted to legal analysis of category “checks and balances” in the scope of constitutional legal coercion.The purpose of the paper is to confirm or disprove hypothesis that mechanism of checks and balances is a method of prevention and resolution of constitutional conflicts.The methodology of the study includes comparative legal method as well as general scientific methods (analysis, synthesis, description) and particular academic legal methods (for-mal-legal method, interpretation of legal acts).The main results and scope of their application. While the Russian legal tradition focused on the search for optimal "checks" and "balances" as well as defended the theoretical model of formalism in this matter, the English legal tradition, on the contrary, focused on finding the optimal functional balance of all branches of government. The system of checks and balances serves the purpose of resolving constitutional and legal conflicts, when it is based on a functional approach rather than a formal one. The factors of “checks and bal-ances” mechanism are:– formation of the three branches of government in different ways;– comparability of powers of the Supreme authorities belonging to various branches of the powers with discrepancy of terms of their powers;– authorities of every branch of government must have "counterbalance" – the powers of compensatory, substituting type – besides it’s traditional powers. The executive and legislative authorities have "quasi-judicial" powers, the executive authorities have "quasi-legislative" powers often.– authorities of every branch of government must have "checks" – possibility to participate in the mechanism of constitutional and legal coercion in relation to another branch of the power.The executive branch can prevent a constitutional conflict generated by a gap or defect of laws through delegated law-making. The executive branch receives "quasi-legislative" powers with delegated law-making. It allows this authorities not only to respond promptly to changing public relations, but also to fill legislative gaps in a timely manner. This "counter-balance" is aimed at preventing constitutional and legal conflicts.Conclusions. The mechanism of checks and balances, which is based on the principle of separation of powers, is the primary way to prevent constitutional and legal conflicts, and also serves the purpose of resolving conflicts that have already arisen. The main manifestations of this function are the presence of compensatory and substitutive powers of various branches of government and the possibility of one branch of government to participate in the mechanism of constitutional and legal coercion in relation to another branch of government.